In Vitro Susceptibility of Ureaplasma urealyticum and Mycoplasma hominis Isolates in Argentina - Jorgelina Smayevsky; Silvia Relloso; Mariela Pundik; Alejandra Lanza; Gabriela Weltman; Carlos Bantar; Hebe Bianchini (Hindawi Limited, 1995)
Objective: Our goal was to determine the in vitro susceptibility of Ureaplasma urealyticum and Mycoplasma hominis isolates to several antibiotics in Argentina.